Variables associated with Besnoitia tarandi prevalence and cyst density in barren-ground caribou (Rangifer tarandus) populations - Côté, Steeve D.; Beauchamp, Guy; Brodeur, Vincent; Kutz, Susan; Taillon, Joëlle; Simard, Manon; Ducrocq, Julie; Lair, Stéphane (Journal of Wildlife Diseases, 2020)
Besnoitia tarandi has been documented in free-ranging reindeer and caribou (Rangifer tarandus spp.) since 1922 throughout their arctic and subarctic ranges; however, very little is known about its epidemiology. We evaluated variables associated with B. tarandi prevalence and cyst density with the use of barren-ground caribou (Rangifer tarandus) from two migratory herds in northern Quebec: the Rivière-aux-Feuilles and the Rivière-George herds. Diagnosis of infection was made upon the microscopic observation of characteristic cysts in a formalin-fixed section of skin from the anterior aspect of the metatarsus. The density of cysts (number of B. tarandi cysts/mm2) was calculated in a section of the dermis extending from the epidermis of the skin to the base of the hair follicles and adnexal structures. Statistically significant associations between B. tarandi prevalence and cyst density, sex, age, and time of harvest were observed. Male caribou had a slightly higher prevalence compared to females, whereas cyst densities were similar between sexes. We found a nonlinear increase in the odds of infection by B. tarandi by age combined with the opposite trend for intensity of infection. Higher B. tarandi prevalence was observed in caribou sampled in the fall compared to June of the same year, suggesting that transmission is increased during the summer. Higher densities of cysts observed during the fall compared to June of the following year may be the result of the elimination of B. tarandi cysts from the dermis during the winter, or lower winter survival of heavily infected caribou. Comparisons of B. tarandi prevalence and density across herds should take into account these different variables.